Estimating sex‐specific abundance in fawning areas of a high‐density Columbian black‐tailed deer population using fecal DNA. Issue 1 (10th December 2014) - Lounsberry, Zachary T.; Forrester, Tavis D.; Olegario, Maryjo T.; Brazeal, Jennifer L.; Wittmer, Heiko U.; Sacks, Benjamin N.
ABSTRACT The recent development of fecal‐genetic capture‐mark‐recapture (CMR) methods has increased the feasibility of estimating abundance of forest‐dwelling ungulates that are difficult to survey using visual methods. Unless genetic markers differentiating sex are incorporated into such studies, however, genetic CMR approaches risk missing sex‐specific differences in population trends. We developed a single‐reaction genetic assay for sex and individual identification, including 10 microsatellites and an SRY marker, and applied it in the context of a post‐fawning CMR study of Columbian black‐tailed deer (Odocoileus hemionus columbianus) in forested habitat of coastal California during 2011 and 2012. We measured sex‐specific abundance and sex ratios in high‐quality summer habitats encompassing 4 distinct fawning areas. We detected a significant interaction between sex and year, indicating different trends in the abundance of males and females. We also detected a significant decline in abundance of females between years (P = 0.045), which agreed with independent telemetry‐based estimates, and significant differences in female abundance among fawning areas (P = 0.020) but no significant differences in the abundance of males for either variable (F1–3, 20 < 0.710, P > 0.410). When sex was not considered in the analysis, we found no significant differences in abundance between the 2 years, suggesting that differing trends between the 2 sexes obscured the female‐specific patterns. We estimated average local (i.e., on the high‐quality summer ranges) density (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2wq27b46" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />D^</alternatives>) for females at 41.0 (± 5.9) deer/km2 in 2011 and 29.1 (± 6.8) deer/km2 in 2012, and local density of males at 15.7 (± 3.0) deer/km2 across the 2 study years. Accordingly, sex ratios differed between years (95% CI = 3.0–4.2 F:M ratio in 2011, 2.0–2.3 F:M ratio in 2012). Incorporating sex and individual markers into a single assay provided a cost‐effective means of applying CMR estimation based on fecal DNA to a high‐density ungulate population in a forested ecosystem and emphasized the importance of explicitly modeling sex in abundance estimation. © 2014 The Wildlife Society.